Choline Intake Was Mildly Associated With Hypertension Among Older Adults in Cross-Sectional NHANES 2011–2014. (7th June 2021) - Taesuwan, Siraphat; Thammapichai, Paradee; Ganz, Ariel; Jirarattanarangsri, Wachira; Khemacheewakul, Julaluk; Leksawasdi, Noppol
Abstract: Objectives: The study objective is to investigate the relationships of choline intake with blood pressure (BP) and hypertension among U.S. adults aged ≥65 y using the sample from the 2011–2014 National Health and Examination Survey (NHANES). The association between choline-containing supplement usage and BP in adults aged ≥20 y was also assessed to confirm previous findings. Methods: The cross-sectional associations of choline intake with prevalent hypertension ( n  = 2113) and BP ( n  = 843) were assessed among the NHANES older adults using logistic and multiple linear regression models for complex surveys, respectively. Logistic regression was used to test the association between supplemental choline use and prevalent hypertension in adults aged ≥20 y ( n  = 9561). Effect modification by sex, race/ethnicity, body mass index (BMI) and comorbidity were also investigated. Results: Among older adults, choline intake interacted with BMI ( P -interaction = 0.04) such that choline intake tended to be associated with lower odds of hypertension among people with BMI lower than 18.5 kg/m 2 (odds ratio [95% Confidence Interval], OR [95% CI]: 0.64 [0.4, 1.00]; P  = 0.052). Choline intake was not associated with systolic BP. In contrast, its relation to diastolic BP differed by comorbidity ( P -interaction = 0.03) with a negative direction of association observed among those who were free of comorbidities and a positive direction observed among those with comorbidities. No association was found between choline supplement use and the odds of hypertension. Conclusions: Collectively, these results suggested that the associations of choline intake with BP levels and hypertension risk among older adults are mild and dependent on other risk factors. A higher choline intake may be beneficialy associated with BP among people who have healthier profiles. Funding Sources: This study was supported by the Young Faculty Research Grant, Faculty of Agro-Industry, Chiang Mai, Thailand.